The October 2019 Protest Movement in Iraq. An Analysis of the ’Early Moments’ of the Mobilisation - Lovotti, Chiara; Proserpio, Licia (PARTECIPAZIONE E CONFLITTO, 2021)
On 1 October 2019, a wide-ranging anti-government protest took to the streets in Baghdad. Grievances included unemployment, a lack of basic services, the absence of social justice, and endemic corruption in political and economic institutions. Despite swift and severe state repression, the protest snowballed into a countrywide mobilisation encompassing the central-southern governorates to become the largest protest movement to challenge Iraq’s post-2003 political order. By granting analytical weight to the role of early riser activists, this paper focuses on the factors that shaped activists’ decisions and lead to different forms of spontaneous participation involving both sympathisers and bystanders. In so doing, it draws attention to the non-hierarchical structure of the movement and its "diffused communication" strategy, the repression as a "moral shock" and the rhetoric of protest slogans. At the crossroads between social movement studies and Iraqi studies, this article contributes to both bodies of scholarship with empirical research. On one hand, it enriches social movement literature by shedding light on strategies and actions adopted by activists operating in non-liberal contexts. On the other hand, it enriches Iraqi political studies by demonstrating that the country hosts a vibrant sphere of contentious politics, a sphere that deserves ample scrutiny.